Movement Patterns of Transient and Prolonged Positioning Events in Nursing Home Residents: Results from the TEAM-UP Trial. (1st December 2022) - Gadhoumi, Kais; Sonenblum, Sharon Eve; Kennerly, Susan M.; Alderden, Jenny; Sharkey, Phoebe D.; Horn, Susan D.; Yap, Tracey L.
ABSTRACT: OBJECTIVE: To characterize transient and prolonged body position patterns in a large sample of nursing home (NH) residents and describe the variability in movement patterns based on time of occurrence. METHODS: This study is a descriptive, exploratory analysis of up to 28 days of longitudinal accelerometer data for 1, 100 NH residents from the TEAM-UP (Turn Everyone and Move for Ulcer Prevention) clinical trial. Investigators analyzed rates of transient events (TEs; less than 60 seconds) and prolonged events (PEs; 60 seconds or longer) and their interrelationships by nursing shift. RESULTS: Residents' positions changed for at least 1 minute (PEs) nearly three times per hour. Shorter-duration movements (TEs) occurred almost eight times per hour. Residents' PE rates were highest in shift 2 (3 pm to 11 pm ), when the median duration and maximum lengths of PEs were lowest; the least active time of day was shift 3 (11 pm to 7 am ). Three-quarters of all PEs lasted less than 15 minutes. The rate of TEs within PEs decreased significantly as the duration of PEs increased. CONCLUSIONS: The NH residents demonstrate complex patterns of movements of both short and prolonged duration while lying and sitting. Findings represent how NH residents naturally move in real-world conditions and provide a new set of metrics to study tissue offloading and its role in pressure injury prevention.